2013
DOI: 10.1155/2013/805456
|View full text |Cite
|
Sign up to set email alerts
|

DGGE Identification of Microorganisms Associated withBorrelia burgdorferiSensu Lato- orAnaplasma phagocytophilum-InfectedIxodes ricinusTicks from Northwest Norway

Abstract: Ticks acquire a wide range of microorganisms as a natural part of their lifecycle. Bacteria, viruses, and protozoa can be transmitted to ticks during feeding and free-living phases. DGGE profiling is a molecular method to describe the microbial population associated with ticks and demonstrate some of the complexity and variety of tick-borne microorganisms. The present study profiled a total of 120 I. ricinus ticks, which were divided into three equally sized groups. We found that B. burgdorferi s.l.-infected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In this study, the 100% prevalence rate of FLEs-Hd in field colony is significantly higher than those reported previously in other tick species 14 16 . There is also a fantastically stable vertical transmission of FLEs-Hd throughout the entire life cycle of H. doenitzi , which is in accordance with the FLEs in D. variabilis and D. albipictus 26 35 . These data demonstrate that FLEs is an important symbiont and may contribute to the fitness of H. doenitzi .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In this study, the 100% prevalence rate of FLEs-Hd in field colony is significantly higher than those reported previously in other tick species 14 16 . There is also a fantastically stable vertical transmission of FLEs-Hd throughout the entire life cycle of H. doenitzi , which is in accordance with the FLEs in D. variabilis and D. albipictus 26 35 . These data demonstrate that FLEs is an important symbiont and may contribute to the fitness of H. doenitzi .…”
Section: Discussionsupporting
confidence: 71%
“…Sphingomonas and Acinetobacter were characterized as the main bacteria in H. doenitzi , and a novel Francisella -like endosymbiont was identified and further analyzed . Sphingomonas bacteria have been reported in I. ricinus, I. ovatus, I. persulcatus and H. flava by assays of bacterial communities 26 27 . Acinetobacter is known as environmental contaminant commonly found in soil, and some Acinetobacter species that are typical representatives of nosocomial infections have been found in ticks 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite alcohol washing, some of the bacteria may have survived, perhaps in crevices of the exoskeleton not reachable by the alcohol. Bacteria from the genera Staphylococcus, Bacillus, Corynebacterium, Klebsiella and Rothia, some of which isolated in this study, were reported across many tick species (Andreotti et al, 2011;Carpi et al, 2011;Tveten et al, 2013;Clow et al, 2018;Ruiling et al, 2019), suggesting that these bacteria may have a role in the biology of the tick or the transmission of tick pathogens.…”
Section: Discussionmentioning
confidence: 56%
“…Recent advances in sequencing technologies and bioinformatic methods, the polymerase chain reaction (PCR) and denaturing gradient gel electrophoresis (PCR-DGGE) method has been very popular for bacteria detection in many animals (Schabereiter-Gurtner et al 2003;Kušar et al 2012;Moreno et al 2006). In spite of their significance as pathogens, little information is available about identification of intestinal bacterial flora in ticks using PCR-DGGE (Schabereiter et al 2003;Van Overbeek et al 2008;Tveten et al 2013;Xu et al 2015). Moreover, there has been no report of intestinal bacterial flora in H. flava ticks using PCR-DGGE in China.…”
Section: Introductionmentioning
confidence: 99%